Physiological and prognostic differences between types of exercise stress echocardiography for functional mitral regurgitation. Issue 1 (22nd April 2021) - Kagiyama, Nobuyuki; Toki, Misako; Yuri, Takuya; Aritaka, Shingo; Hayashida, Akihiro; Sengupta, Partho P; Yoshida, Kiyoshi
Abstract : Objective: Secondary mitral regurgitation (MR) demonstrates dynamic change during exercise. This prospective observational study aimed to compare exercise stress echocardiography (ESE) where handgrip exercise (handgrip-ESE) or semisupine ergometer exercise was performed (ergometer-ESE) for patients with secondary MR. Methods: Handgrip-ESE and symptom-limited ergometer-ESE were performed for 53 patients (median age (IQR): 68 (58–78) years; 70% male) on the same day. Baseline global longitudinal strain (GLS) was 9.2% (6.0%–14.0%) and MR volume was 20 (14–26) mL. All-cause death and cardiac hospitalisation were tracked for median 439 (101–507) days. Results: Handgrip-ESE induced slightly but significantly greater degrees of MR increase (median one grade increase; p<0.001) than ergometer-ESE, although the changes in other parameters, including GLS (+1.1% vs −0.6%, p<0.001), were significantly smaller. Correlations between the two examinations with respect to the changes in the echocardiographic parameters were weak. Kaplan-Meier analyses revealed poor improvement in GLS during ergometer-ESE, but not the change in MR, was associated with adverse events (p=0.0065). No echocardiographic change observed during handgrip-ESE was prognostic. After adjusting for a clinical risk score, GLS changes during ergometer-ESE remained significant in predicting the adverse events (HR 0.39, p=0.03) A subgroup analysis in patients with moderate or greater MR at baseline (n=27) showed the same results as in the entire cohort. Conclusions: The physiological and prognostic implications of handgrip-ESE and ergometer-ESE findings significantly differ in patients with left ventricular dysfunction and secondary MR. The type of exercise to be performed in ESE should be carefully selected.